DESAIN DAN SIMULASI PEMBEBANAN STATIK SASIS KENDARAAN LISTRIK OTONOM TANPA KEMUDI UNTUK INDIVIDUAL MOBILITY MENGGUNAKAN SOFTWARE SOLIDWORK - ricky, 240103; Witanto, Yovan; Supardi, Nurul Iman; Syabanda, Yukhi Mustaqim Kusuma (UNIB Press, 2024)
The chassis or frame is the internal framework that serves as the basis for producing an object, supporting parts such as the engine or electronic components of the object. The chassis can be likened to the skeletal structure of animals.Electric cars are vehicles powered by electrical energy stored in batteries or other energy storage devices. Electric cars were very popular in the late 19th and early 20th centuries, but their popularity waned due to advancements in internal combustion engine technology and the decreasing cost of gasoline-powered vehicles. SolidWorks is a software application based on automation for creating 3D solid models to explore the use of Windows graphics. Using this software is not very difficult, depending on the user's willingness as an engineer to learn it. This software is highly useful in engineering for creating both 3D and 2D models. Additionally, SolidWorks can perform simulations that are highly beneficial for conducting research on machines or materials.